Novel Lubricant Compressor For Automotive Air Conditioning System - Azmi, W. H. (2017)
Outside Temperature increase – Global warming, El-Nino, etc. Cooling capacity reduce – Compressor work increase Automotive Air Conditioning (AAC) – increase fuel Consumption up to 20% & Greenhouse gas NOx (80%) & CO (70%) Current AAC system is been optimized but still could not cope with today’s weather condition.